Development of flexible PVDF/PAMPS polyelectrolyte proton conductive membrane. (2020) - Debbarma, Lima; Panwar, Varij; Khanduri, Priya; Panwar, Lokesh Singh
Abstract: Progresses in the field of proton conducting polymers have grown very rapidly. A summary of technological growth involving proton conducting polymers indicates that this research area expands at unexpected rates. The paper first introduces the proton conducting polymers and introduces its applications such as used in fabrication of electronic device, thin film transistor (TFT), solar energy conversion, artificial muscles, rechargeable batteries, and solar energy conversion. In this paper, we present and analyse the conductivity of Polyvinylidene fluoride (PVDF)/poly (2-acrylamido-2-methyl-1-propane sulfonic acid) (PAMPS) in frequency range 20 Hz–10 MHz for lithium-ion batteries and battery separator applications. Membrane showing high conductivity has been synthesized by blending PVDF and PAMPS together. Initially the conductivity of pure PVDF membrane was low, but it increased with the addition of PAMPS. The impedance analyser was used to measure dielectric constant, AC conductivity and dissipation factor. In this research paper we have concluded that on adding 60% wt of PAMPs to PVDF; we have got the best result in terms of dielectric constant and conductivity.